2015
DOI: 10.3109/0142159x.2015.1009023
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of professional behaviour and academic outcomes in a UK medical school: A longitudinal cohort study

Abstract: Measures of a range of relevant selection attributes and personal qualities can predict intermediate and end of course achievements in academic, clinical and professional behaviour domains. In this study HYMS academic score, some UKCAT subtest scores and the total UKCAT score, and some non-cognitive tests completed at the outset of studies, together predicted outcomes most comprehensively. Tutor evaluation of students early in the course also identified the more and less successful students in the three domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…Powis and colleagues developed the Personal Qualities Assessment (PQA: which includes the IVQ and ITQ) and tested it in a number of centres. However, few of the reported studies have examined the predictive validity of the PQA, and those which have been carried out are limited in their methodology (e.g., small scale, local outcome measures e.g., Adams et al 2012Adams et al , 2015Dowell et al 2011;Manuel et al 2005) and-at best-find only modest correlations (Adams et al 2012(Adams et al , 2015. We would argue that, given the evidence to date as to the utility of SJTs in a variety of professional groups (see earlier, and Patterson et al 2012a, b for a review) the use of a validated SJT as an outcome measure is more robust than the comparators used by other authors, and hence the weak relationship we found is probably a more accurate assessment of the power of the IVQ and ITQ to predict outcomes at the end of medical school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Powis and colleagues developed the Personal Qualities Assessment (PQA: which includes the IVQ and ITQ) and tested it in a number of centres. However, few of the reported studies have examined the predictive validity of the PQA, and those which have been carried out are limited in their methodology (e.g., small scale, local outcome measures e.g., Adams et al 2012Adams et al , 2015Dowell et al 2011;Manuel et al 2005) and-at best-find only modest correlations (Adams et al 2012(Adams et al , 2015. We would argue that, given the evidence to date as to the utility of SJTs in a variety of professional groups (see earlier, and Patterson et al 2012a, b for a review) the use of a validated SJT as an outcome measure is more robust than the comparators used by other authors, and hence the weak relationship we found is probably a more accurate assessment of the power of the IVQ and ITQ to predict outcomes at the end of medical school.…”
Section: Discussionmentioning
confidence: 99%
“…These can be grouped into ''paper and pencil'' assessments of personality traits (e.g., Adams et al 2012Adams et al , 2015Bore et al 2005a, b;Dowell et al 2011;Fukui et al 2014;James et al 2013;Lumsden et al 2005;Manuel et al 2005;Nedjat et al 2013), structured multiple interview approaches (Dore et al 2010;Eva et al, 2004aEva et al, , b, 2009Hofmeister et al 2008Hofmeister et al , 2009O'Brien et al 2011;Reiter et al 2007;Roberts et al 2008;Rosenfeld et al 2008), selection centres (Gafni et al 2012;ten Cate and Smal 2002;Ziv et al 2008;Gale et al 2010;Randall et al 2006a, b) and-the ''new kid on the block''-situational judgement tests (Christian et al 2010;Koczwara et al 2012;Lievens 2013;Lievens et al 2008;Patterson et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas academic outcomes are always recorded, there is a need for objective measures of professional Selecting medical students behaviour and competence. Some data are available for PQA and other measures of non-cognitive qualities (Adam et al 2012(Adam et al , 2014.…”
Section: Non-cognitive Testsmentioning
confidence: 99%
“…5 In this article, we focus on non-academic skills. However, it is not always clear whether the constructs measured by non-academic tests should be considered skills, traits, or a combination of both.…”
Section: Introductionmentioning
confidence: 99%